Brand Awareness Strategy: Role of Blackberry Messenger(Case in Sumber Tiket Murah Travel: PIN 2144C41F) - Dian Pane; Baroroh Lestari (UBL, 2013)
The purposes of this research is to explore the role of Blackberry Messenger (BBM) as one of marketingcommunication`s tool by analyzing Sumber Tiket Murah travel strategy in advertising its brand. BBM belongs toBlackberry Smartphone application and nowdays recently used as mobile sales promotion. The level of brandawareness is the output based on four stages e.g recognition, recall, top of mind, brand dominance. It used aqualitative approach using a written interview to gather information through 10 (ten) informants as the sample.The stages of data analysis were followed by data collection and subsequent data reduction which wasimplemented to present the data and drawing conclusions. Particular attention was given to analyze the role ofBBM as one of the marketing communication which expressed through BBM and also as shown in the qualitativeresearch interview.The analysis concludes that there were four main conclusions. The result from the interview showed that theinformants were aware about Sumber Tiket Murah as a travel agent provides the cheapest price for airline ticketstheir purchased. They also stated that Sumber Tiket Murah was proper to referenced to colleagues or friends.Moreover, the results also indicate that they found ticket information from other agents (eg. MMBC, TerminalTiket and others). But another informants were also loyal to Sumber Tiket Murah. It was because Sumber TiketMurah have some uniqueness, such as trustworthy, always provide cheaper tickets, discount prices, salepromotion by quiz, and can perform other transactions besides selling airlines ticket.Based on this research Sumber Tiket Murah has reached the stage brand recall. The travel experience showsthat maintaining consumers more difficult than look for new customers. Although informants stated they awareabout Sumber Tiket Murah travel because of its uniqueness, but Sumber Tiket Murah has not become thedominant brand among informants yet. Therefore, Sumber Tiket Murah need to have unique characteristics thatare spesific, such as providing souvenirs from various regions in Indonesia. Otherwise, Sumber Tiket Murah mustbe able to maintain uniqueness that already exist today. Moreover, by expanding the lines of business, it willincrease brand awareness of Sumber Tiket Murah.